Mutations of the integrin αIIb/β3 intracytoplasmic salt bridge cause macrothrombocytopenia and enlarged platelet α‐granules. Issue 2 (17th November 2017) - Favier, Marie; Bordet, Jean‐Claude; Favier, Remi; Gkalea, Vasiliki; Pillois, Xavier; Rameau, Philippe; Debili, Najet; Alessi, Marie‐Christine; Nurden, Paquita; Raslova, Hana; Nurden, Alan
Abstract: Rare gain‐of‐function mutations within the ITGA2B or ITGB3 genes have been recognized to cause macrothrombocytopenia (MTP). Here we report three new families with autosomal dominant (AD) MTP, two harboring the same mutation of ITGA2B, αIIbR995W, and a third family with an ITGB3 mutation, β3D723H . In silico analysis shows how the two mutated amino acids directly modify the salt bridge linking the intra‐cytoplasmic part of αIIb to β3 of the integrin αIIbβ3. For all affected patients, the bleeding syndrome and MTP was mild to moderate. Platelet aggregation tended to be reduced but not absent. Electron microscopy associated with a morphometric analysis revealed large round platelets; a feature being the presence of abnormal large α‐granules with some giant forms showing signs of fusion. Analysis of the maturation and development of megakaryocytes reveal no defect in their early maturation but abnormal proplatelet formation was observed with increased size of the tips. Interestingly, this study revealed that in addition to the classical phenotype of patients with αIIbβ3 intracytoplasmic mutations there is an abnormal maturation of α‐granules. It is now necessary to determine if this feature is a characteristic of all mutations disturbing the αIIb R995/β3 D723 salt bridge.